Belinostat exerts antitumor cytotoxicity through the ubiquitin-proteasome pathway in lung squamous cell carcinoma - Kong, L.; Tan, T.; Ong, W.; Bi, C.; Huynh, H.; Lee, S.; Chng, W.; Eichhorn, Pieter; Goh, B. (Elsevier, 2017)
© 2017 The Authors. Published by FEBS Press and John Wiley & Sons Ltd. There have been advances in personalized therapy directed by molecular profiles in lung adenocarcinoma, but not in lung squamous cell carcinoma (SCC). The lack of actionable driver oncogenes in SCC has restricted the use of small-molecule inhibitors. Here, we show that SCC cell lines displayed differential sensitivities to belinostat, a pan-histone deacetylase inhibitor. Phosphoproteomic analysis of belinostat-treated SCC cells revealed significant downregulation of the MAPK pathway, along with the induction of apoptosis. In cisplatin-resistant cells that demonstrated aberrant MAPK activation, combined treatment with belinostat significantly inhibited cisplatin-induced ERK phosphorylation and exhibited strong synergistic cytotoxicity. Furthermore, belinostat transcriptionally upregulated the F-box proteins FBXO3 and FBXW10, which directly targeted son of sevenless (SOS), an upstream regulator of the MAPK pathway, for proteasome-mediated degradation. Supporting this, suppression of SOS/ERK pathway by belinostat could be abrogated by inhibiting proteasomal activity either with bortezomib or with siRNA knockdown of FBXO3/FBXW10. Taken together, these preclinical data offer a novel understanding of the epigenetic mechanism by which belinostat exerts its cytotoxicity and supports the combination with cisplatin in clinical settings for chemorefractory SCC tumors.